(untitled) (Web of Teachers: Inderscience Research, 2024)
As mentioned above, the educational task is to organize, repeat or reinforce a topic through games. Through the game, it will be possible to perform this task without realizing it. As for the educational aspect, in the course of the game, qualities such as cooperation, discipline, diligence, hard work, and completion of the started work are brought up in the students. Through the game, students’ thinking develops, their creative abilities increase, qualities such as quickness and responsiveness are formed.In general, the didactic game has a positive effect on the overall psychological state of the lesson. Kotarinki’s mood helps to overcome difficulties in acquiring knowledge. The characteristic of didactic games is that it increases children’s activity and initiative, teaches them to believe in independence and little strength. Also, children’s will and character are formed during this month. The child is accustomed to honesty, correctness, teamwork and action. Subjects that are difficult to learn are easily learned through didactic games. Through regular and consistent use of didactic games, children’s ability to become independent increases, their interest in science increases, they are able to observe, compare, summarize and draw conclusions.